Undergraduates’ needs and seeking behaviour: A preliminary study - Mohd Nadzir, Maslinda; Abd Wahab, Alawiyah; Othman, Nafishah (International Foundation for Research & Development, 2015)
Information seeking behaviour refers to the process of how individual identify their information needs, search and use the information identified to support their work. Understanding the needs and seeking for information from different types of information sources is very important to student in completing their research activities. This paper presents findings from a preliminary study of undergraduate students’ information seeking behaviour and their need of information for their research project. The aim of this study is to identify their information seeking behaviour in finding the required information that meet their information needs. A survey was carried out and thirty nine final year students from two related Information Technology (IT) programs in a Higher Learning Institution in Malaysia returns the questionnaires. Findings indicate that information about development tools was the most important information needed by the students for finishing research project. In searching for required information, Google search engine was found to be the most widely used by the students. Furthermore, most students preferred to use the electronic information sources to search information due to the variety of information available on the Web.